APPROACHES TO THE FORMATION OF REGION COMPETITIVENESS - Svetlana Sergeevna Berman (Наука Красноярья, 2016)
Within the conditions of integration processes strengthening and interdependency of economical agents at micro-, meso- and macro levels in the hierarchy of competitiveness the problem of its enhancing for regional social and economic systems acts as a strategic benchmark of national economies development. This is justified by the fact that regions are independent subjects of market relations, where strategic goals, focused on satisfaction of population social and economic needs, are realized and in persuasion of these needs the most predominant meaning is given to regions competitiveness. Considering tense social and economic situation existing in our country, the needs for improvement of approaches to development and usage of effective instruments of regions competitiveness management, as well as approaches to the formation of estimation methods of their competitiveness level represent the current priority. Purpose: to conduct analysis of approaches to the formation of of regions competitiveness, to develop theoretical model of regions competitiveness management. Methodology: a systematic approach based on general scientific methods of empirical and theoretical studies, such as: comparison, analysis and synthesis, modeling techniques. Results: basic criteria for the definition of the term “regions competitiveness” are determined; model of competitiveness management at the regional level was developed; tasks, that can be solved used the abovementioned model, are defined. Practical implications: the model, developed by the authors, can be used by regional authorities at analysis of their competitive positions, in identification of key regions-competitors, as well as at elaboration of strategic development documents.